Kampanye 'Love Myself' dari BTS : Memanfaatkan Media 4.0 untuk Menyebarkan Pesan Positif tentang Cintai Diri dan Anti-Kekerasan - Mellysa Indika Putri; Azzahra Balqis Luqyana; Noni Permata Susanto (Jurnal Kemitraan Masyarakat, 2025)
Advances in technology and social media have changed the way individuals obtain information and interact, especially in the context of global culture. BTS, a famous South Korean boy band, utilized social media to build a strong relationship with their fans, ARMY, through the campaign “Love Myself.” The campaign emphasized the importance of self-love and raised issues of mental health and violence. The campaign emphasized the importance of self-love and raised issues of mental health and violence. Through platforms such as Twitter and Instagram, BTS interacted directly with ARMY, who responded with significant support, including a 2.4 billion won donation to UNICEF. This interaction not only strengthened the online community but also helped boost fans' confidence. This research analyzes the impact of the “Love Myself” campaign on ARMY's engagement in social issues through social media. Furthermore, the resulting impact provides important insights into how celebrities and social media can influence broader social change. The campaign also reflects a shift in traditional ways of advocating and supporting social issues.